APLIKASI LAYANAN JUAL BELI DAN JASA SERVICE KOMPUTER BERBASIS WEBSITE PADA CV YAKUSA COMP: PERANCANGAN APLIKASI WEBSITE MARKETPLACE - Jibran el Fansyuri; Yoga Febriatala; Riska Hapipah; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The online electronic buying/selling website is an ordering marketplace as well as services engaged in technology. Along with the development of websites on smartphones in the online field, it greatly affects the interest of buyers to use smartphones today. Remembering customers in CV. Yakusa Comp, who also wants to repair their electronic devices by submitting a complaint, we will help direct, and if the customer wants to sell, buy or trade, they can directly use our service, so that the buyer will feel bored from waiting and can just move to another place. So to deal with the above problems, we took the initiative to build a Marketplace platform which can be a place where customers can easily access them anywhere and anytime by designing an online website that can bring together sellers and buyers. The results of the research are to provide efficiency for customers who are outside the area to solve problems with their electronic devices, without having to wait and help customers sell their electronic goods, of course with competitive prices and quality.